Pelatihan Pengenalan Flight Instrument & Lighting System Pada Pesawat Terbang - Nina Hendrarini; Simon Siregar; Duddy Soegiarto4; Ema ema (Politeknik Caltex Riau, 2025)
Revitalization of Vocational High Schools (SMK) is the core of Presidential Instruction (Inpres) Number 9 of 2016 on Vocational Education, which emphasizes the importance of mastering applied expertise in specific fields. Vocational education requires students to master both theory and practical implementation through learning. The lack of practical facilities in SMK is caused by the high cost of providing advanced equipment, the rapid development of technology, minimal cooperation with industry, limited competent teaching staff, and suboptimal government support. As a result, students do not get adequate practical experience, which impacts their readiness to enter the aviation industry after graduation. In order to support the program to improve students' abilities and readiness, the Faculty of Applied Sciences conducted training aimed at providing insights and improving the competencies of students of SMKN 12 Bandung. The focus of this training is on instrumentation and lighting. Thus, it is expected that students can apply this knowledge in the ever-evolving world of business and industry and contribute effectively to creating a more modern and efficient learning environment in schools. Keywords: Instrumentation; Lighting; Vocational